2014
DOI: 10.1523/jneurosci.2571-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interactions of the SMA and Cingulate Cortex Sustain Premovement Activity for Voluntary Actions

Abstract: Voluntary action is one of the core functions of the human brain, and is accompanied by the well known readiness potential or Bereitschaftspotential. A network of cortical areas is responsible for the motor preparation process, including the anterior mid-cingulate cortex (aMCC) and the SMA. However, the relationship between activity in these regions during movement preparation and the readiness potential is poorly understood. We examined this relationship by integrating simultaneously acquired EEG and fMRI thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 58 publications
11
55
0
3
Order By: Relevance
“…Results confirmed that the BP is well detectable and originated from the combined activity of the SMA and the CMA, which have reciprocal interactions, in order to sustain pre-movement activity for voluntary actions (Nguyen et al, 2014). Moreover, the pN component was localized in the bilateral pars opercularis of the iFg.…”
Section: Prefrontal Activitysupporting
confidence: 60%
“…Results confirmed that the BP is well detectable and originated from the combined activity of the SMA and the CMA, which have reciprocal interactions, in order to sustain pre-movement activity for voluntary actions (Nguyen et al, 2014). Moreover, the pN component was localized in the bilateral pars opercularis of the iFg.…”
Section: Prefrontal Activitysupporting
confidence: 60%
“…The BP consists of two parts (Kornhuber and Deecke, 1965; Shibasaki and Hallett, 2006): The early phase (BP proper, “early BP”) is a slow, non-lateralized negative shift, probably generated in the supplementary motor area (SMA) and anterior neighboring areas (pre-SMA and anterior mid-cingulate cortex; Deecke and Kornhuber, 1978; Deecke et al, 1987; Ball et al, 1999; Cunnington et al, 2002, 2003; Shibasaki and Hallett, 2006; Nguyen et al, 2014). In the late phase (about 400 ms before the movement) this BP proper is overlapped by lateralized potentials that reflect activity of the motor cortex controlling the moving limb (Kornhuber and Deecke, 1965; Kutas and Donchin, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…According to findings in the neurophysiology of act-sound coupling, listening to sounds that are part of one's motor repertory can involve co-representation of similar motor pathways; it would also seem that ecological relevance and urgency plays a role in modulating the degree to which we mirror the heard actions of others (Aglioti & Pazzaglia, 2010;Kohler et al, 2002). SMA has been implicated in internally generated movement, coordination of action sequences, and postural stability (Nguyen, Breakspear, & Cunnington, 2014), in addition to vividness of auditory imagery (Halpern et al, 2004;Lima et al, 2015), while the pre-and primary motor cortices are the main regions involved in action planning and execution.…”
Section: Discussionmentioning
confidence: 99%